Bond graph modeling of a 3-joint string-tube actuated finger prosthesis. (November 2017) - Mishra, Neeraj; Vaz, Anand
Highlights: Modeling of a prosthetic 3-joint finger mechanism using Bond graph is presented. String-tube based joint actuation for under-actuated prosthesis is demonstrated. Subsystem interactions through power and causal representation are understandable. Word Bond Graph Objects used for subsystem representation are explained in detail. Abstract: In prosthetic systems, the mechanism, sensing and actuation systems, and controls are some of the important areas which require modeling and analysis. Causal representation based on power transactions provides better understanding of interactions between these subsystems. A unified approach is therefore required to deal with the dynamics of such systems. Bond graph offers such a unified approach to the dynamics of such biomechanical systems. The concept of Word Bond Graph Objects (WBGOs) provides several advantages in modeling such large systems, including: compact representation; facilitation of understanding of energetic and causal interactions between component subsystems; algorithmic, quick and easy object oriented programming for numerical simulations. The approach had been applied earlier to develop models for a class of hand prosthesis. This work is an elaborate extension to a redundant under-actuated three-joint string-tube based finger prosthesis for a partially impaired hand. It systematically explains the dynamics of behavior of the mechanism, interactions at translational and revolute couplings between rigid phalanges, and, string-tube based joint actuation principles involved in this class of prosthesis through simulations of the bond graph models.